2018
DOI: 10.1007/s12035-018-0889-z
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 Halts Remote Neuroinflammation and Improves Functional Recovery after Focal Brain Damage Via ALX/FPR2 Receptor-Regulated MicroRNAs

Abstract: Remote damage is a secondary phenomenon that usually occurs after a primary brain damage in regions that are distant, yet functionally connected, and that is critical for determining the outcomes of several CNS pathologies, including traumatic brain and spinal cord injuries. The understanding of remote damage-associated mechanisms has been mostly achieved in several models of focal brain injury such as the hemicerebellectomy (HCb) experimental paradigm, which helped to identify the involvement of many key play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 46 publications
1
93
0
Order By: Relevance
“…The neuroprotectors, resolvin D1, and aspirin‐triggered resolvin D1 improve brain functions and impair neuronal death by downregulating NF‐kB, TLR4, CD200, and IL6R (Bisicchia et al, 2018; Recchiuti et al, 2010). They induce remote functional recovery after brain damage (Bisicchia et al, 2018).…”
Section: Roles Of Dha and Its Metabolites In Brain Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroprotectors, resolvin D1, and aspirin‐triggered resolvin D1 improve brain functions and impair neuronal death by downregulating NF‐kB, TLR4, CD200, and IL6R (Bisicchia et al, 2018; Recchiuti et al, 2010). They induce remote functional recovery after brain damage (Bisicchia et al, 2018).…”
Section: Roles Of Dha and Its Metabolites In Brain Functionmentioning
confidence: 99%
“…The neuroprotectors, resolvin D1, and aspirin‐triggered resolvin D1 improve brain functions and impair neuronal death by downregulating NF‐kB, TLR4, CD200, and IL6R (Bisicchia et al, 2018; Recchiuti et al, 2010). They induce remote functional recovery after brain damage (Bisicchia et al, 2018). Resolvin D2 and aspirin‐triggered resolvin D2 protect from cerebral ischemic injury through ERK1/2 phosphorylation followed by stimulation of nNOS or eNOS to inhibit programmed neuronal cell death and increase zonula occludens‐1 for the maintenance of blood‐brain barrier integrity (Zuo et al, 2018).…”
Section: Roles Of Dha and Its Metabolites In Brain Functionmentioning
confidence: 99%
“…Although microglia express a wide range of lipid‐sensitive receptors and lipid metabolism‐related genes (Mauerer, Walczak, & Langmann, ; Mecha et al, ), the molecular link between bioactive fatty acids and their effects in microglia has not been completely clarified yet. Emerging evidence suggests that PUFAs can drive a protective phenotype through the activation of CB2, which is among microglial receptors reprogramming microglia toward beneficial function (Guida et al, ; Mecha et al, ; Nunez et al, ) but other receptors may be involved including ALX/FPR2 receptors (Bisicchia et al, ) (Figure ).…”
Section: Alimentary Components Driving Pro‐regenerative Microglia Funmentioning
confidence: 99%
“…Of note, whether such DHA‐induced neuroprotective effects are mediated by this fatty acid alone or by its derived and specialized pro‐resolving mediators (SPMs) have yet to be unraveled. The discoveries that several DHA‐derived SPMs, such as resolvins or neuroprotectins, play critical roles in modulating microglia responses as well ad in the modulation of reactive species is suggestive of their possible involvement in controlling neuroplasticity and in representing a link between the immune and the central nervous systems. In addition, our findings show that even in the absence of inflammatory stimuli or without the induction of specific diseases, systemic DHA deficiency induces a basal inflammatory activity, which is characterized by an overall upregulation of several inflammatory markers; however, this only has a little impact on behavioral functions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the role of DHA in inflammation is already consolidated and is receiving greater attention mainly due to the discovery that it serves as a metabolic precursor for a new genus of anti‐inflammatory molecules, that is, resolvins, neuroprotectins, and maresins, that are involved in the spontaneous but active process of resolution of inflammation, which mainly involves myeloid cells such as macrophages and glial cells . Indeed, we have recently shown that the impairment of systemic DHA synthesis in Elovl2 −/− mice, delineates an immunophenotypical alteration of M1/M2 macrophages, with M1 being more pro‐inflammatory and M2 less protective, supporting the view that DHA has a relevant role in controlling inflammatory responses .…”
Section: Introductionmentioning
confidence: 99%